2020
DOI: 10.1364/optica.409886
|View full text |Cite
|
Sign up to set email alerts
|

Ghost diffraction holographic microscopy

Abstract: Unconventional systems that adopt the concept of ghost schemes have led to advancements in some imaging applications. However, their application in quantitative phase imaging remains a challenge. Here, we introduce a basis for quantitative phase imaging with ghost diffraction and demonstrate ghost diffraction holographic microscopy for complex-valued imaging. We achieve this by introducing an off-axis holography approach in the modified ghost diffraction system. We also realize a correlation hologram in the cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(20 citation statements)
references
References 58 publications
0
20
0
Order By: Relevance
“…com/article/10.3390/app112412167/s1. References [28,[31][32][33][34]37] are cited in the supplementary materials.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…com/article/10.3390/app112412167/s1. References [28,[31][32][33][34]37] are cited in the supplementary materials.…”
Section: Discussionmentioning
confidence: 99%
“…From Equation (3), it is evident that this intensity cross-correlation retrieves only the modulus of W(r 1 , r 2 ); therefore, for the complex correlation function recovery and thereby the simultaneous recovery of amplitude and phase distributions of the OAM mode, we make use of the holography scheme, where a reference random field is combined with the propagated spatially incoherent field as shown in Figure 1. The independent addition of the holographic reference random field [31,32] (ψ R (r)) with the field contributions ψ m (r) and ψ 0 (r) modifies the correlation of intensity fluctuations in Equation (3) to:…”
Section: Generation and Recovery Of Oam Modesmentioning
confidence: 99%
See 1 more Smart Citation
“…The other is single-pixel camera (SPC), where the target is usually imaged onto a spatial modulation device and the modulated signals are received by a single-pixel detector [6,7]. In comparison with SPC, more investigations were focused on GI because of its potential applications in remote sensing [10][11][12], three-dimensional imaging [13][14][15], phase imaging [16][17][18][19], optical encryption [20,21], and microwave imaging [22]. Recently, some works have demonstrated that SPC has more advantages than GI in remote sensing [8,9,[23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…The deep neural networks can solve many remaining problems in fields of scattering imaging, computational ghost imaging, Fourier laminar microscopic imaging, phase retrieval and hologram data compression etc. [5][6][7][8][9][10][11]. It is shown that as an object passes through a scattering medium or multimode fiber (MMF), the information of the image is deteriorated.…”
Section: Introductionmentioning
confidence: 99%